2005
DOI: 10.1590/s1519-566x2005000200022
|View full text |Cite
|
Sign up to set email alerts
|

Trichomycete fungi (Zygomycota) associated with mosquito larvae (Diptera: Culicidae) in natural and artificial habitats in Manaus, AM Brazil

Abstract: Neotropical Entomology 34(2): 325-329 (2005) Fungos Trichomycetes (Zygomicota) Associados com Larvas de Mosquitos (Diptera: Culicidae) emCriadouros Naturais e Artificiais em Manaus, AM PALAVRAS-CHAVE: Inseto aquático, Smittium culisetae, criadouro, infecção de larvas, Amazônia CentralABSTRACT -Fungal species of the class Trichomycete fungi (Zygomycota) are associated with the digestive tracts of Arthropoda. The relationships between these fungi and their hosts are still little understood: they may be comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 15 publications
(12 reference statements)
2
18
0
1
Order By: Relevance
“…Studies on entomopathogenic fungi have shown their promise as biological control agents of mosquito vectors of tropical diseases (Messias 1989).There are many examples worldwide related to the interactions of fungi and Culicidae larvae (e.g. Agarwala et al 1999, Lucarotti & Shoulkamy 2000, Scholte et al 2004, Pereira et al 2005. However, the present paper is the fi rst study of Hyphomycetes fungi associated with Culicidae larvae in the Brazilian Amazon region.…”
mentioning
confidence: 78%
“…Studies on entomopathogenic fungi have shown their promise as biological control agents of mosquito vectors of tropical diseases (Messias 1989).There are many examples worldwide related to the interactions of fungi and Culicidae larvae (e.g. Agarwala et al 1999, Lucarotti & Shoulkamy 2000, Scholte et al 2004, Pereira et al 2005. However, the present paper is the fi rst study of Hyphomycetes fungi associated with Culicidae larvae in the Brazilian Amazon region.…”
mentioning
confidence: 78%
“…Fungi can occasionally attack insects or develop symbiotic relationships (3). Many interactions between fungi and mosquitoes have been reported worldwide (4)(5)(6)(7)(8)(9)(10). Other interactions between bees and fungi have been documented, as well (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…The high abundance of Cx. urichii had not yet been recorded in previous studies of mosquito ecology in the Brazilian Amazon [45,46], however, at low frequencies, this species can be observed in natural and artificial breeding sites in forest areas of the Manaus municipality, Amazonas [47,48]. Trichoprosopon digitatum , followed by Cx .…”
Section: Discussionmentioning
confidence: 99%